In loco provision of physical therapy services to military firefighters involved in Brumadinho dam disaster - Marcelo von Sperling de Souza; Anna Florence Alves Paulino de Souza; Pollyanna Figueiredo Gomes; Bárbara Brito de Carvalho e Borges; Roseane Marques Ribeiro; Maria Rosália de Faria Moraes (Einstein (São Paulo), 2022)
ABSTRACT Objective To investigate the impact of in loco physical therapy interventions on military firefighters involved in search and rescue operations following the collapse of the Brumadinho dam, in Minas Gerais. To describe the clinical and demographic profile of military firefighters receiving physical therapy care. Methods Physical therapy assessment and care protocols were designed. Protocols were based on manual physical therapy approaches, and aimed primarily to alleviate musculoskeletal pain. Physical therapists involved were duly trained prior to interventions to level technical skills. Physical therapy was provided upon request (i.e., military workers sought the service after work shift completion). Results A total of 318 military firefighters, most of whom were males (92.5%) mean age 32.9 years, received physical therapy care (575 sessions spread out over 48 days). In this sample, 43.4% of military workers had a history of musculoskeletal complaints. Military workers seeking physical therapy after completion of their work shifts reported mean pain intensity of 5.4 in a numerical scale. Spinal pain was reported in 61.7% of cases, followed by generalized muscle and myofascial pain (16.7%), lower and upper limb pain (14.4% and 6.8%, respectively). At the end of sessions, mean pain intensity reported dropped down to 1.3. Differences were statistically significant (non-parametric Wilcoxon test; p=0.001). Conclusion The unprecedented physical therapy intervention described had a positive impact on relief of musculoskeletal pain among military firefighters involved in search and rescue operations during the Brumadinho dam disaster, and seen at the end of their work shifts.